Immunity benefits of yoga and physical exercises in the era of COVID-19 Pandemic - Karuppasamy Govindasamy; Chandrababu Suresh; Mithin Anand; Saran KS; Mou Pramanik; Dilpreet Kaur; Imen Achouri; Hiba Boughanmi (H.S. Skovoroda Kharkiv National Pedagogical University, 2022)
Purpose. The novel coronavirus is the recently emerged disease of the respiratory system for which various national and international research agencies are putting joint efforts towards finding a permanent cure. Recently, the vaccine against coronavirus has been designed by various pharmaceutical agencies that are currently undergoing clinical trials. Since vaccines prevent infection by strengthening the defense system of the body, we proposed that yoga and physical exercises could act as an integrative approach to synergize the immunogenic response of the coronavirus vaccine. Yoga and physical exercises are already known to boost immunity against several other infections. Materials and Methods. In the present review article, we aimed towards exploring the role of yoga and physical exercise as an immunity booster against coronavirus infection. Being India is a low-income country, yoga and physical exercises could be an excellent cost-effective strategy that could be administrated along with vaccine trials to enhance immunity against virus infection. Results. In the present review, we analyze the studies conducted to date focusing on finding the role of yoga and physical exercises to prevent coronavirus infection. We also described the potential exercises, which are already known to enhance the immunity of the body by particularly targeting respiratory disease. Conclusion. The present review article will help in providing the health agencies potential targets, which could further be explored to established a standard exercise module to enhance the vaccine-mediated immunity against coronavirus infection.